Odpowiedzi

2010-03-03T16:41:36+01:00
A) 4a+4b = 4(a+b)
b) 3x+15y = 3(x+5y)
c) 7x+14y = 7(x+2y)
d) 17x²-17 = 17(x^-1)
e) bc-bd = b(c-d)
f) xy-3x = x(y-3)
g) cy-c = c(y-1)
h) 9xy-12y = 3y(3x-4)
i) ab+ab² = ab(1+b)
j) 3by+6b = 3b(y+2)
k) 6a-24b+30c = 6(a-4b+5c)
l) 2xy+3x-x²y = x(2y+3-xy)

3(a-2) = 3a-6
-4(x+y) = -4x-4y
m(2m+3) = 2m^+3m
3p(2p+5p-1) = 6p^+15p^-3p = 21p^-3p
2010-03-03T16:45:05+01:00
A) 4a+4b = 4(a + b)
b) 3x+15y = 3(x + 5y)
c) 7x+14y = 7(x + 2y)
d) 17x²-17 = 17(x² - 1)
e) bc-bd = b(c - d)
f) xy- 3x = x(y - 3)
g) cy-c = c(y - 1)
h) 9xy-12y = 3y(3x - 4)

i) ab+ab² = ab(1 + b)
j)3 by + 6b = 3b(y + 2)
k) 6a-24b+ 30c = 6(2a - 4b + 5c)
l) 2xy+ 3x - x²y = x(2y + 3 - xy)
WYKONAJ MNOZENIE
3(a-2) = 3a - 6
-4 (x+y) = - 4x - 4y
m(2m+3) = 2m² + 3m
3p(2p+5p-1) = 6p² + 15p² - 3p = 21p² - 3p